Strategies Of Economic Development: Micro, Macro, And Mesoeconomic Levels (The Ukrainian Case) - (:unkn) unknown (Quality - Access to Success, 2023)
The study is extremely necessary for the economy of Ukraine. In the period of war, it is necessary to have an effective strategy of economic development, regulating the activities at all levels of economic development of the state. The study used the correlation and regression analysis and the method of SWOT-analysis, which allowed to evaluate the National economic strategy developed by the state until 2030 with its adjustment during the war. The economic development strategy is divided into micro-, meso-, macroeconomic levels. At each level, the directions of development of all systems are defined. Ukraine has a very large potential for economic development. Military actions allow the state to attract foreign investment and find reliable partners among foreigners. But the war has taken away the industrial regions and there is a need to specialize production in safer regions of the state. A successful economic development strategy will select the most promising and significant factors.The purpose of the research of the article was to determine the strategy of economic development of Ukraine during the war. The selected areas of research: assessment of the National economic strategy by 2030 and its possible application for the period of war; the main directions of economic development strategy for use during the war; the effectiveness of the proposed directions of development strategy of economic development. The conclusion reflects the main directions of the economic development strategy proposed for use in the war with certain vectors of development at the micro-, macro-,and meso-economic levels. The results of the SWOT-analysis are clearly described and compared with the strategic directions in the National Economic Strategy until 2030. Proposed directions for the implementation of actions in each development environment.
Keywords: strategy, economic development, microeconomic level, mesoeconomic level, macroeconomic level, SWOT-analysis, economic development vectors, economic audit